Resistência de união de um sistema adesivo universal à superfície de materiais híbridos para CAD/CAM - Bettiol, Heloisa Pressi (2019)
Purpose: This in vitro study evaluated the tensile bond strength of a universal adhesive system to the surface of hybrid CAD/CAM materials treated with: Er:YAG laser, 10% fluoridric acid and Al2O3 sandblasting. Material and methods: One hundred and twenty samples were made with two restorative CAD/CAM materials (Lava Ultimate and Vita Enamic), resulting in 60 samples of each material, divided into 8 groups (n= 15) according to the surface treatments: Lava Ultimate: LU - Control, LAL - Sandblasting with Al2O3, LAC - 10% hydrofluoric acid, LER - Laser Er: YAG; Vita Enamic: EC - Control, EAL - Sandblasting with Al2O3, EAC - 10% hydrofluoric acid, EER - Laser Er: YAG. After the surface treatments the samples received silane (except control), and universal adhesive (Single Bond Universal) were applied and a resin cement RelyX Ultimate (3M ESPE) cone was built. The samples were submitted to tensile bond strength test until rupture between the materials and the failure patterns were analyzed. Results: The highest mean of bond strength in MPa were: EAL (65.94A ± 43.54), EAC (63.78A ± 40.1), LAC (56.40A ± 22.5) followed by LU (44.50AB ± 27.5), LAL (41.6AB ± 23.84) and LER (35.93AB ± 15.65). The lowest values were for EER (23,40B ± 13,8) and EC (20,10B ± 18,30) groups. The means followed by the same letter do not present statistical difference for ANOVA two-way and Tukey (p> 0.05). The failure analysis showed a predominance of adhesive failure for Lava Ultimate and adhesive and cohesive failures for Vita Enamic. Conclusion: There was no more effective treatment for Lava Ultimate in relation to its control. Both conditioning with 10% hydrofluoric acid and aluminum oxide sandblasting proved to be effective for Vita Enamic.